2019
DOI: 10.1021/acs.energyfuels.9b02865
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Biochar Formation during Slow Pyrolysis in the Presence of Alkali Metal Carbonate Additives

Abstract: In this work, slow pyrolysis of sawdust of Eucalyptus pilularis biomass and ternary molten carbonate eutectic [Li2CO3, 43.5%; Na2CO3, 31.5%; and K2CO3, 25% (mole percentage)] in thermogravimetric analysis at three different temperatures, 600, 750, and 900 °C, was studied. These salts affect the slow pyrolysis process, including changes in the volatile release mechanism and the morphology of remnant char material. The initial results show that, in the presence of molten carbonate, biomass particles make bubble-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 62 publications
0
20
0
Order By: Relevance
“…Eucalyptus pilularis (Blackbutt) sawdust and Sigma kraft lignin 19,41 were used as biomass samples with particle size range 75–150 μm. The ternary eutectic was blended in the mole percentage Li 2 CO 3 : 43.5%, Na 2 CO 3 : 31.5%, K 2 CO 3 : 25% from Sigma-Aldrich (melting point at ∼400 °C) and prepared in the same procedure of previous work.…”
Section: Materials and Methodologymentioning
confidence: 99%
See 4 more Smart Citations
“…Eucalyptus pilularis (Blackbutt) sawdust and Sigma kraft lignin 19,41 were used as biomass samples with particle size range 75–150 μm. The ternary eutectic was blended in the mole percentage Li 2 CO 3 : 43.5%, Na 2 CO 3 : 31.5%, K 2 CO 3 : 25% from Sigma-Aldrich (melting point at ∼400 °C) and prepared in the same procedure of previous work.…”
Section: Materials and Methodologymentioning
confidence: 99%
“…Studies on three fundamental components of biomass structure (hemicellulose, lignin, cellulose) suggest a temperature range of 250 °C to 700 °C to accomplish complete devolatilization. 16,17 It is also reported that, at elevated temperatures, the morphology of remnant char improves by generation of a porous structure, 18,19 higher surface area, 20,21 and induced ordering of graphitic nanostructures. 22–24 Thus, not only the rate of heating is crucial in biochar preparation but also the final highest heating temperature has significant impacts on resultant char structure.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations